2004
DOI: 10.1016/j.surfcoat.2004.08.036
|View full text |Cite
|
Sign up to set email alerts
|

CVD and CVI of pyrocarbon from various precursors

Abstract: International audienceThe control of pyrocarbon (pyC) chemical vapor infiltration (CVI) is a key issue in the processing of high-performance C/C composites with applications in aerospace parts and braking technology. For years, the precise investigation of deposition kinetics and pyC nanometerscale anisotropy has been rehearsed in chemical vapor deposition (CVD) and several variants of CVI with various pore sizes, and using mostly propane, propylene, and methane as source precursors. A literature survey and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(55 citation statements)
references
References 40 publications
5
50
0
Order By: Relevance
“…More details on the synthesis of such pyrocarbons are given by Vignoles et al [31]. Le Poche et al [6] have shown than Regenerative laminar pyrocarbon is deposited when the maturation of the gazeous phase is high enough to produce large planar aromatic species, which are deposited by physisorption onto the substrate prior to form pyrocarbon.…”
Section: Raman Microspectroscopymentioning
confidence: 99%
“…More details on the synthesis of such pyrocarbons are given by Vignoles et al [31]. Le Poche et al [6] have shown than Regenerative laminar pyrocarbon is deposited when the maturation of the gazeous phase is high enough to produce large planar aromatic species, which are deposited by physisorption onto the substrate prior to form pyrocarbon.…”
Section: Raman Microspectroscopymentioning
confidence: 99%
“…1 The process is commonly defined as CVD for chemical vapour deposition (CVI for infiltration). 2 As far as CVI is concerned, cracking reactions are conducted in order to avoid carbon black nucleation by lowering the pressure down to 1 to 10 kPa and the temperature around 1000 °C. These conditions favour mass transfer with respect to chemical deposition; consequently the homogeneity of the deposit within a preform is enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…CH 3 attacks propene will produce CH 4 with a barrier of 80.9 kJ/ mol at 298.15 K or of 181.4 kJ/mol at 1200 K. These reactions are as follows: The reaction branching in (11)-(13) has a rate branching ratio of 1.7 3 10 40 at 298.15 K and of 4.1 3 10 10 at 1200 K. This is also large enough for the reaction to proceed in this path. The ratio for reaction (14) is 688.8 at 298.15 K and is much smaller a value of 3.2 at 1200 K. However, this does not affect the formation of CH 4 because all the next higher TSs (TS107, TS108, and TS110) are linking the same product CH 4 as shown in Figure 2c. Figure 16 shows that the reactions for the decomposition of C 2 -bearing species are H Á þ C 2 H 6 ðIM21Þ !…”
Section: Proposal Of the Most Favorable Pathsmentioning
confidence: 92%
“…2,[9][10][11][12][13] Propene (C 3 H 6 ) is extensively used as the volatile hydrocarbon (carried with H 2 gas) for preparing PyC in CVD or CVI with high-deposition rate. 14,15 This system has been investigated experimentally [16][17][18][19][20][21][22][23][24][25][26][27][28] and theoretically with numerical simulations. [29][30][31] Also as an interesting and useful reaction in dehydrogenization and cracking of hydrocarbons, the pyrolysis process has formed a topic of several investigations.…”
Section: Introductionmentioning
confidence: 99%